Health Systems Strengthening Efforts Help to Improve the Delivery of Maternal Nutrition Interventions in Antenatal Care in Uttar Pradesh (UP), India but Gaps Remain. (29th May 2020) - Kachwaha, Shivani; Nguyen, Phuong; Tran, Lan Mai; Avula, Rasmi; Young, Melissa; Ghosh, Sebanti; Escobar-Alegria, Jessica; Frongillo, Edward; Menon, Purnima
Abstract: Objectives: Frontline workers (FLWs) deliver essential nutrition services to reduce maternal undernutrition in India, but coverage and quality remain sub-optimal. Alive & Thrive aimed to strengthen delivery of interpersonal counselling, community mobilization and micronutrient supplements through the government antenatal care (ANC) platform in UP. We studied pathways through which the nutrition-intensified ANC (I-ANC) was intended to impact FLWs capacity, knowledge, and service delivery, compared to standard ANC (S-ANC). Methods: We used a cluster-randomized design with cross-sectional surveys at baseline (2017) and endline (2019), ∼500 FLWs per survey. Differences between I-ANC and S-ANC were compared along six impact pathway components (training, availability of materials, supportive supervision, knowledge, service delivery, and counselling content) using mixed-effects regression adjusted for clustering. Results: Training exposure was higher in I-ANC than S-ANC (9 percentage points, pp). Nutrition training topics were low-moderate (30–60%) in both arms. Job aids were more available in I-ANC (70–80%) than S-ANC (30–40%). Supply of iron-folate and calcium supplements were low in both arms, with 10–50% having stock-outs. FLWs in I-ANC were more likely to receive supervision visits (7 pp), but gaps remained in both arms. Compared to S-ANC, FLWs in I-ANC had higher knowledge on diet diversity (6 pp), adequate intake (10 pp), iron-folate (10 pp) and calcium supplements (30 pp), pregnancy weight gain (20–30 pp), and early breastfeeding (5 pp), but similarly low knowledge of exclusive breastfeeding. ANC check-ups by FLWs were 20 pp higher in I-ANC. FLWs in I-ANC did more counselling on adequate diet, supplements, and weight gain (10–20 pp). Counselling on diet diversity and breastfeeding were low in both arms. Conclusions: Health systems strengthening efforts helped improve the delivery of maternal nutrition interventions in antenatal care in this context, but gaps remain. Several health system elements along the program pathway – supply chain management, training, supervisory practices – require strengthening to further improve FLW knowledge and nutrition service delivery. Funding Sources: Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI 360.